Dam Cedar Creek? (Symphony in the Flint Hills, 2018)
Introduction: For more than seventy years, engaged Flint Hills citizens have battled to stop a federal reservoir project at Cedar Creek, near Cedar Point. In late 2017, at the age of ninetysix, Pat Sauble’s life-long devotion to water conservation was recognized by the governor, who presented him with a Water Legacy Award. In 1976, Sauble was featured in the following article in Kansas Farmer-Stockman. (Originally published in Kansas Farmer-Stockman magazine, October 1976, now known as Kansas Farmer.)